ASSISTANCE IN CREATING CANVA-BASED LEARNING PRESENTATION MEDIA FOR TEACHERS OF STATE ELEMENTARY SCHOOL 5 IN SYAMTALIRA ARON - Bahri, Samsul; Husna, Asmaul; Rahmat, Rahmat; Rahmati, Rahmati; Sandy, Cut lika Mestika (Universitas Muhammadiyah Aceh, 2023)
The purpose of this activity is to provide knowledge to Elementary School 5’s teachers in Syamtalira Aron about how to create Canva-based learning presentation media. The method we apply is direct assistance to teachers in the process of creating Canva-based Learning Presentation Media. Our team will provide intensive guidance to assist teachers in mastering the use of Canva and designing effective presentation media. The expected outcome of this service activity is to offer substantial support to teachers, enabling them to independently create learning presentation media that suit their needs. By focusing on Canva as a creative tool, we want to ensure that teachers can optimize the use of presentation media in their learning process. Through this assistance, it is hoped that teachers will acquire not only new knowledge but also practical skills in creating engaging and effective learning materials. It is hoped that this assistance can offer sustainable solutions for teachers in addressing the challenges of modern learning. Keywords: Mentoring, Learning Presentation Media, Canva.